“Nanobook” as Specific Form of Modern Russian Literature - I. S. Samokhin; N. L. Sokolova; M. G. Sergeyeva (Научный диалог, 2018)
The specific form of modern Russian literature - the so-called “nanobook” - is considered. The relevance of the study is due to the emergence of a significant number of such works in the late 2000s and the first half of the 2010s, as well as insufficient attention to this phenomenon from scientific community. A review of nanobooks presented to readers in print or electronic form in the post-Soviet period is proposed. The appeal to such material is the novelty of this study. The authors conclude that nanobook is not a literary genre, but a literary form. It is noted that such works do not have stable features in a content, but they can be combined into a single group on the basis of certain formal characteristics: short body of the main text; “reproduction” of a lexical unit in a line or in a column for tens or even hundreds of pages; author’s equating of his / her work to large prose or poetic statements, for example, novels, poems, epics; publication of such a work by a separate edition. In addition, the authors of the article emphasize that the importance of a title, subtitle, overtitle, preface, dedication, epigraph, afterword in a nanobook increases significantly, while the importance of the main body of the book, on the contrary, decreases.